CAR-T Cell Therapy in Gastrointestinal Cancer, Head and Neck Cancer, and Autoimmune Diseases: Current Advances and Future Perspectives - Martyna Kania; Hanna Bartkowiak; Damian Grubski; Agnieszka Adamowska; Filip Nadolny; Julia Janecka; Jędrzej Jabłoński; Alicja Śniatała; Michał Hofman; Adam Dudek (Journal of Education, Health and Sport)
Introduction: Chimeric Antigen Receptor (CAR) T cell therapy has revolutionized cancer treatment, showing significant success in hematologic malignancies. However, its application in solid tumors like gastrointestinal (GI) and head and neck cancers, as well as autoimmune diseases, remains a challenge. The development of CAR-T cell therapy for these indications presents unique difficulties, including tumor heterogeneity, antigen specificity, and immune suppression within the tumor microenvironment.